The Pak Budi Concept in Transformational Leadership of Madrasah Principals to Improve Student Achievement - Manyingarri Alfianoor Ibrahim; Muhammad Fahim Tharaba (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
This study aims to explore and analyze how the transformational leadership of the principal at Madrasah Ibtidaiyah Negeri (MIN) 2 Malang City is formulated through the PAK BUDI concept (Attention, Appreciation, Communication, Integrity, Updates/Publication, Engaging parents, and Inspiration) and its impact on improving student achievement. The study employed a qualitative approach with a case study design. Data were collected through observations, in-depth interviews with the principal, teachers, students, and parents, as well as documentation studies of school programs, activity reports, and student achievement records. Data validity was ensured through triangulation of sources, techniques, and time. Data analysis followed an interactive model consisting of data condensation, data display, and conclusion drawing. The results indicate that PAK BUDI represents the practical implementation of transformational leadership, reflected in personal attention to school members, consistent appreciation, open two-way communication, integrity through transparent and accountable services, publication of achievements as a form of public accountability, strengthened partnerships with parents, and inspiring role modeling by the principal. These practices contributed to increased student discipline and learning motivation, stronger academic programs and systematic monitoring of learning progress, and improved non-academic achievement through competitions and extracurricular activities. In addition, a culture of achievement and a strong sense of school belonging involving teachers, students, and parents were established. The findings confirm that context-based and humane transformational leadership can serve as an effective driver for improving student achievement at the primary education level.